SEMANTIC AND STRUCTURAL FEATURES OF “GET” AND “BE” IN PASSIVE VOICE CONSTRUCTION IN ENGLISH (American Journal of Research in Humanities and Social Sciences, 2025)
The passive voice is a vital syntactic construction in English, often used for emphasizing the action or its receiver rather than the doer. While the be-passive is traditionally discussed, the get-passive structure has become increasingly prominent in both spoken and informal written English. This paper explores the syntactic, semantic, and pragmatic functions of the get-passive, drawing on previous scholarly work and authentic language data. The study employs the EMRAD (Introduction, Methods, Results, and Discussion) structure to systematically analyze the formation, usage contexts, and implications of this alternative passive voice.